Health Literacy Grades of Individuals Applicable to A University Hospital in Türkiye - ÇELİK DURMUŞ, Serpil; ERDEM, Yurdagül (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2025)
Being healthy is everyone's fundamental right. For this purpose, states, institutions providing health services and individuals have very important duties. Health literacy is defined as the ability of an individualistic to understand and interpret this information and act accordingly when an individualistic is asked to provide medical information. This study was conducted in a descriptive manner to examine the health literacy grade of individuals applying to a university hospital. Data were collected with the Descriptive Characteristics Information Form and the Türkiye Health Literacy Scale (TSOY-32). Ethics committee approval for the research and written consent were obtained from the participants. 167 volunteer individuals were included in the research. It was determined that the Health Literacy grade of 97% of the participants was insufficient. It is important to direct individuals to health education and health promotion programs or to organize training on these issues in hospitals.